Etiudy animowane Grzegorza Wacławka - Adam Domalewski (Images)
The author considers in the paper three animated etudes made by Grzegorz Wacławek in Film School in Łódź. Films entitled Gleam, Scrap and Lost share many common features: creation of the hero’s outer world, extensive use of symbolism and condensation of events centered around one or two heroes. Particularly interesting mean used by Wacławek in endings of the films is the transformation of the presented world that can be named a scale change. Also on this basis director’s animations are metaphorically interpreted, showing their existential meaning, close to the tradition of Polish Animation School.